A comparative analysis of green building rating systems in China and the United States. (June 2023) - Li, Xianglin; Feng, Wei; Liu, Xiaojing; Yang, Yue
Highlights: A thorough analysis of Chinese green building rating systems in contrast with LEED. Track the system evolution of the GBRSs to analyze the development trend. Collect projects big data sets to analyze the laws of technology application in green buildings. Provide a set of policy recommendations to further improve China's green building standards. Abstract: Several studies have compared green building rating systems (GBRSs) in China and the United States, Nonetheless, few studies included in-depth analysis on specific rating tools with project specific data validating green building technologies and actual performance. This study conducted a comprehensive data-driven comparison of the GBRSs of China and the United States. The goal was to understand the current status and further improve China's GBRS and promote green building technologies. The study first conducted thorough comparisons of GBRSs in China and the U.S. by selecting a series of distinct rating tools. Then, it analyzed each tool's development objectives, contents, and rating score settings. The comparison concludes the future development needs for China's GBRS. In addition to standard comparison, green building technologies applied in certified projects were also summarized. The results demonstrated that GBRSs in both China and the U.S. reflect well the technical paths to achieve green building sustainable development. By analyzing certified projects, it was also found that the incremental costs of green building technologies were controllable. Finally, based on the comparison and case analysis, the study provide a set of policy recommendations to further improve China's green building standards.